TUNNELING, DETERMINANT CORPORATE TURNAROUND - Animah Animah (Jurnal Aplikasi Akuntansi, 2017)
The objective of this study is to analyze the factors that affect corporate turnaround when a company experiencing financial distress. Idependent variables used in this research are severity company, company size, expenses retrenchment, CEO turnover and dependent variable corporate turnaround. The research sample consisted of 12 financial sector companies listed on the Indonesia Stock Exchange during 2008-2010. Data were collected by using purposive sampling method. The hypothesis testing based on multiple linear regression analysis. The result of date analysis indicated that the variableof severity company, company size, expenses retrenchmentand CEO turnover simultaneously affect the corporate turnaround. Partially, only variablecompany of size was found to have influence on corporate turnaround. Meanwhile, severity company, expenses retrenchment and CEO turnover were found to have on the corporate turnaround. R Square value shows that the no influence ability of the four independent variables in explaining the corporate turnaround success was 31.6% and the varians of corporate turnaround success 68.4% were explain by other factors that explain.